2014
DOI: 10.4238/2014.october.20.3
|View full text |Cite
|
Sign up to set email alerts
|

Study of polymorphic variants of the serotonin 2A receptor gene (5-HT2A) and its possible effects on smoking habits of a population from northeastern Brazil

Abstract: ABSTRACT. Previous studies have revealed a genetic component, including genetic polymorphisms in the serotonergic pathway, particularly in the serotonin receptor gene (5-HT2A). The aim of this study was to investigate associations of the T102C (rs6313) and A-1438G (rs6311) polymorphisms with tobacco use in a population from northeastern Brazil. We evaluated these polymorphisms in 135 nonsmokers and 135 smokers using polymerase chain reaction-restricted fragment length polymorphism. The distribution of allele a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The rs6313∗C allele carriage is associated with decreased expression of 5-HT2A receptors. In different studies, either C or T alleles were associated with smoking status and intensity [23, 24]. The frequency of rs6313∗TT genotype in Ukraine is 11.3%, the data correspond to the Finnish population, as well as to mixed groups of European, South American, African, and South Asian origins.…”
Section: Resultsmentioning
confidence: 90%
“…The rs6313∗C allele carriage is associated with decreased expression of 5-HT2A receptors. In different studies, either C or T alleles were associated with smoking status and intensity [23, 24]. The frequency of rs6313∗TT genotype in Ukraine is 11.3%, the data correspond to the Finnish population, as well as to mixed groups of European, South American, African, and South Asian origins.…”
Section: Resultsmentioning
confidence: 90%
“…Considering specifically the T102C‐SNP, some investigations described the relationship between the CC genotype or C allele and schizophrenia (Ni et al, ; Vaquero‐Lorenzo et al, ), suicidal behavior (González‐Castro et al, ), alcohol dependence, impulsivity of alcohol dependent‐patients (Jakubczyk et al, ; Wrzosek et al, ), and relapse after alcohol dependency treatment (Jakubczyk et al, ). Associations between CC genotype and smoking (Prado‐Lima et al, ) and nicotine dependence level (Ramos‐Neto et al, ) were also reported. The CC genotype was reported to be associated with Alzheimer's disease (Fehér et al, ) and the occurrence of hallucinations, delusions, psychosis, and aberrant motor behavior in Alzheimer's patients (Pritchard et al, ).…”
Section: Introductionmentioning
confidence: 91%
“…The T102C SNP occurring in this gene can produce three genotypes: TT, CC, and TC. Previous studies have described an association between the CC genotype, that shows 20% less receptor density on cell membranes, and neuropsychiatric disorders such as schizophrenia (Ni, Lu, Wu, Chen, Yi, & Zhang, ; Vaquero‐Lorenzo et al, ), psychotic symptoms in Alzheimer's patients (Fehér et al, ), and alcohol and tobacco addiction (Jakubczyk et al, ; Prado‐Lima et al, ; Ramos‐Neto et al, ; Wrzosek et al, ). Dysfunctions of the 5‐HT2A receptor also include brain diseases such as migraine headaches, anxiety, and mental depression (Fidalgo et al, ).In addition, problems with 5‐HT2A can cause cardiovascular diseases related to platelet aggregation and abnormal vascular smooth muscle cell physiology (Machida, Iizuka, & Hirafuji, ).…”
Section: Introductionmentioning
confidence: 99%